PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN KERIPIK TEMPE - Murti, Niken Restu; Sundari, Ristina Siti; Heryadi, D Yadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The Covid-19 pandemic has caused some food businesses to experience a decline in sales; where the pandemic occurred, and the enactment of the lockdown rules made a business suffer losses. However, it is different from the "Puja Rasa" tempe chip craftsmanship business, which during the Covid-19 pandemic, experienced an increase in sales volume in 2021. This study aimed to determine how the marketing mix influences the sales volume of "Puja Rasa" tempe chips so that the business can survive and experience an increase in the sales volume of tempeh chips. The research uses a quantitative approach with interviews and documentation methods. The research sample was 80 respondents and consumers of Tempe chips "Puja Rasa" using a random sampling technique and an analytical model using multiple linear regression. The results in this study indicate that the marketing mix consisting of products, prices, promotions, distribution channels, people, processes, and physical facilities has an effect on the sales volume of tempe chips at the tempe chips craftsmen "Puja Rasa" and the marketing mix that has the most influence on the sales volume of chips tempe in the tempeh chip SMEs "Puja Rasa" is the price.